2018
DOI: 10.2903/j.efsa.2018.5164
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of residues of fipronil and other acaricides in chicken eggs and poultry muscle/fat

Abstract: Following the detection of fipronil residues in eggs resulting from a misuse of non-approved veterinary medicinal products in poultry farms against red mites, an ad-hoc monitoring programme was set up in the EU. Member States have provided results for 5,439 samples of eggs and chicken muscle/fat which were analysed for fipronil and a number of additional active substances which were proposed by the European Commission to be monitored in view of potential misuse in poultry farms against red mites. The report su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The management of the emergency by the European and national authorities as well as the discussion about the actual risks for consumers received wide media coverage both in the mass media and on the Internet for several weeks following the first news on the alert. Consequently, to protect the health of citizens and reassure public opinion, the EU set up an ad hoc monitoring program to detect improper uses of the insecticide (EFSA, Reich, & Triacchini, 2018). However, even though millions of eggs and tons of egg products were withdrawn from the market during the alert because their contamination exceeded the legal limits, the quantities of fipronil detected were not so high to be actually dangerous for the health of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The management of the emergency by the European and national authorities as well as the discussion about the actual risks for consumers received wide media coverage both in the mass media and on the Internet for several weeks following the first news on the alert. Consequently, to protect the health of citizens and reassure public opinion, the EU set up an ad hoc monitoring program to detect improper uses of the insecticide (EFSA, Reich, & Triacchini, 2018). However, even though millions of eggs and tons of egg products were withdrawn from the market during the alert because their contamination exceeded the legal limits, the quantities of fipronil detected were not so high to be actually dangerous for the health of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Further, spraying can cause stress in the hens; leads to an exposure of the hens and workers to the acaricide; can lead to environmental contamination through e.g., the manure used as fertilizer; and increases the risk of residues in hens and the eggs ( 18 , 133 ). Indeed, studies on European farms revealed the presence of acaricide residues, even of currently unlicensed substances in tissues and organs of hens and in eggs ( 18 , 134 , 135 ). However, current legal limits (MRL), or MRLs in force at the time the product was allowed, were virtually never exceeded.…”
Section: Reduction Of Pesticide Use (Step 6)mentioning
confidence: 99%
“…2). The rst contaminated Fipronil eggs were reported by the end of July in Belgium [14], and soon thereafter in the Netherlands. Farmers who treated their housing system with Fipronil to control red mite infestation were blocked, and consequently, no eggs, hens, or manure could leave the farm.…”
Section: Assumptions and Delimitationmentioning
confidence: 99%